CORAK PEMIKIRAN TAFSIR PADA PERKEMBANGAN AWAL TRADISI TAFSIR DI NUSANTARA ( Hamzah al-Fansuri, Syamsuddin al-Sumatrani dan Abd Rauf al- Singkel) - Miswar, Andi (Rihlah: Jurnal Sejarah dan Kebudayaan, 2016)
The early growth tafsir science tradition in Indonesia, marked by the birth of interpretation toward the sentences of al-Qur’an in the form of sufistik interpretation which is expressed in verses which have tasawuf pattern , which have done by Hamzah al-Fansuri with his student of Syamsuddin Al-Sumatrani as the form of religion recognition through the effort of interpreting and understanding of the holy al-Qur’an as source of religion. Whereas Abd Rauf alSingkel ( a student of Syamsuddin al-Sumatrani) wrote a book ( related to syariat) antitle of Tarjuman al-Mustafid wich become the first copy of al-Qur’an interpretation by using Malay Ianguage in Indonesia. This Masterpiece represented first step in the field of Qur’anic interpretation in Indonesia and become valuable contribution to Islam religion, that is helpful for society in comprehending meaning the sentences of al-Qur’an in local Ianguage.